The Role and Function of Media Institutions in Society in the Digital Age: A Case Study in Indonesia - Syaputra, Imam; Sabri, Yuli (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aims to examine the role and function of media institutions in society in the digital era in Indonesia. Using a qualitative approach using the case study method, this study collected data through indepth interviews with eight sources consisting of journalists, media observers and the general The research results show that media institutions still play a very important role in shaping public opinion and influencing people's decisions in Indonesia. However, the increasingly complex and multi-dimensional role of media institutions in the digital era also poses new challenges and risks, such as the rise of hoaxes, the spread of unverified news, and the problem of personal data security. The role of media institutions in the digital era is also marked by changes in media consumption patterns that are increasingly diverse and heterogeneous. Social media and digital platforms enable citizens to become producers and consumers of media simultaneously, thereby influencing the way media institutions operate and interact with the In the Indonesian context, regulation and the issue of press freedom are important in supporting the role and function of professional and independent media institutions. This research also highlights the important role of society in strengthening social control over media institutions, so as to maintain the quality and integrity of the news delivered. regulation and the issue of press freedom are important in supporting the role and function of professional and independent media institutions. This research also highlights the important role of society in strengthening social control over media institutions, so as to maintain the quality and integrity of the news conveyed. regulation and the issue of press freedom are important in supporting the role and function of professional and independent media institutions. This research also highlights the important role of society in strengthening social control over media institutions, so as to maintain the quality and integrity of the news conveyed